THE MONTESSORI APPROACH TO IMPROVING EARLY CHILDHOOD CREATIVITY AND INDEPENDENCE - oktasriahayu rahayu (CV Grasta Glory, 2026)
Education is a crucial process in developing students’ potential, especially at an early age, when they are at a crucial stage of development. One approach, which emphasizes child-centered learning while allowing freedom within certain limits. This study aims to examine the role of the Montessori approach in fostering creativity and independence at an early age. The method used was a literature review analyzing various relevant sources. The results indicate that the Montessori approach can enhance children’s creativity through exploratory activities. Furthermore, a wellprepared learning environment and the teacher’s role as a facilitator are supporting factors for the successful implementation of this approach. Thus, the Montessori approach plays a crucial role in fostering creativity and independence at an early age, although its implementation still requires teacher preparedness and adequate supporting facilities.